Diversity and environmental drivers of Suillus communities in Pinus sylvestris var. mongolica forests of Inner Mongolia - Liu Rui-xia; Wu You-han; Li Cong; Qiao Yi-hua; Yang Yi-wen; Yan Wei-ping; Yao Qing-zhi (Open Life Sciences)
This study investigates the diversity and distribution of Suillus fungi in Pinus sylvestris var. mongolica (PSM) forests across Inner Mongolia, with a focus on understanding the environmental factors influencing fungal communities. High-throughput sequencing was utilized to analyze soil fungal communities across 12 PSM forest sites, alongside assessments of meteorological variables and soil enzyme activities. Thirteen Suillus species were identified, with S. clintonianus being the dominant species. The diversity of Suillus fungi exhibited significant geographical variation, with diversity decreasing from east to west. Precipitation and leucine aminopeptidase activity were identified as key drivers of fungal distribution. The soil fungal community was predominantly saprotrophic, playing a crucial role in nutrient cycling and ecosystem stability. The findings provide a deeper understanding of the role of ectomycorrhizal fungi in sustaining forest health and offer valuable insights for sustainable forest management and restoration efforts in semi-arid regions.